Greenwashing and bluewashing in the textile industry: Causes, consequences, and solutions for sustainable fashion - Nahid-Ull-islam Md; Hasan Shah Md Maruf; Chowdhury Md Kamrul Hassan; Akter Mahmuda (Tekstilna industrija)
The textile industry is facing a growing issue of greenwashing and bluewashing, which are misleading environmental and social claims made by companies to appeal to customers' environmental and social consciousness. This review examines the causes and consequences of these practices, focusing on the holistic impact on consumers , corporations, stakeholders, and society. The analysis was conducted using various sources, including review papers, case studies, book chapters, and websites, to identify relevant publications. The study explores the concept of greenwashing and bluewashing in fast fashion, their impact on the environment and society. It suggests promoting transparency, accountability, and independent certification in the textile industry to combat these issues. The lack of research on these practices in the industry makes it difficult to understand their effects. The study emphasizes the need for optimal measures to control these practices, aiming to create a sustainable and responsible fashion sector.